Rasionalitas Tindakan Sosial dalam Tradisi Nyadran di Desa Bluru Kidul Kabupaten Sidoarjo - Ridho Tri Winisudo; Agus Machfud Fauzi (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
The fishing community in the Bluru Kidul area has a religious tradition known as the Nyadran Ceremony. This tradition is carried out from generation to generation by the people of Bluru Kidul village as a form of thanksgiving for the crops they get and also as a prayer ritual to get abundant marine products. The activities of the Nyadran ceremony include making tumpengan up to praying together at the meal of Dewi Sekar Dadu as the leuhur there. This Nyadran ceremony is carried out once a year before the fasting month. This research will discuss the rationality of the fishing community towards the religious tradition of Nyadran as a support for the marine products of the people of Bluru Kidul Village, Sidoarjo Regency. The purpose of this research is to find out how the community responds and acts towards the Nyadran religious tradition as a tradition to support their seafood. This study uses a qualitative phenomenological approach. This study uses Max Weber's theory of rationality. The results of this study are there are 4 actions of the fishing community regarding nyadran religious activities. First, because this activity is to get abundance in seafood and also as gratitude to the Almighty. Second, fishing communities follow because it is an inherent tradition for them. third, it is a hereditary tradition carried out by his previous ancestors that must be continued. Fourth, the emotional bond between the fishing community and God regarding the marine products of the fishing community.